Moving day - Cabot, Meg (New York Scholastic Press, 2008)
Nine-year-old Allie Finkle has rules for everything and is even writing her own rule book, but her world is turned upside-down when she learns that her family is moving across town, which will mean a new house, school, best friend, and plenty of new rules
Hurg
5 8
Keywords: Best friends -- Fiction; Moving, Household -- Fiction